Pioneer Tree Bellucia imperialis (Melastomataceae) from Central Amazon with Seedlings Highly Dependent on Arbuscular Mycorrhizal Fungi - Bento, Ricardo Aparecido (Journal of Fungi, 2023)
Bellucia imperialis is one of the most abundant pioneer tree species in anthropized areas of the Central Amazon, and has ecological importance for the environmental resilience of phosphorus (P)-depleted areas. Thus, we investigated whether B. imperialis depends on symbiosis with arbuscular mycorrhizal fungi (AMF) to grow and establish under the edaphic stresses of low nutrient content and low surface moisture retention capacity of the substrate. We tried three AMF inoculation treatments: (1) CON—no mycorrhizae; (2) MIX—with AMF from pure collection cultures, and (3) NAT—with native AMF, combined with five doses of P via a nutrient solution. All CON treatment seedlings died without AMF, showing the high mycorrhizal dependence of B. imperialis. Increasing P doses significantly decreased the leaf area and shoot and root biomass growth for both the NAT and MIX treatments. Increasing P doses did not affect spore number or mycorrhizal colonization, but decreased the diversity of AMF communities. Some species of the AMF community showed plasticity, enabling them to withstand shortages of and excess P. B. imperialis was shown to be sensitive to excess P, promiscuous, dependent on AMF, and tolerant of scarce nutritional resources, highlighting the need to inoculate seedlings to reforest impacted areas. © 2023 by the authors.
Keywords: Inoculants; Mycotrophic species; Phosphorus; Reforestation; Seedlings